Three new Psammothidium species from lakes of Olympic and Cascade Mountains in Washington State, USA - Enache, Mihaela D.; Potapova, Marina; Sheibley, Rich; Moran, Patrick (Phytotaxa, 2013)
Populations of several Psammothidium species were found in core sediments from nine remote, high elevation, ultraoligotrophic and oligotrophic, Olympic and Cascade Mountain lakes. Three of these species, P. lacustre, P. alpinum, and P. nivale, are described here as new. The morphology of the silica frustules of these species was documented using light and scanning electron microscopy. We discuss the similarities and differences with previously described Psammothidium species.